Historia - moralidad - progreso: apuntes sobre la actualidad filosófica de la Ilustración escocesa - Rosales Rodríguez, Amán (Anales del Seminario de Historia de la Filosofía, 2003)
In this paper, the author offers an interpretation of the present day philosophical significance of the Scottish Enlightenment. After a broad review of the main characteristics of that movement and of the thought of major Scottish figures of the 18th century, the author proposes that contemporary debates concerning the nature and perspectives of progress in history could derive benefit from a critical reconsideration of some views put forth by the Scottish literati.